2012
DOI: 10.1016/j.brainres.2011.05.061
|View full text |Cite
|
Sign up to set email alerts
|

Logic, language and the brain

Abstract: What is the role of language in human cognition? Within the domain of deductive reasoning, the issue has been the focus of numerous investigations without the emergence of a consensus view. Here we consider some of the reasons why neuroimaging studies of deductive reasoning have generated mixed results. We then review recent evidence suggesting that the role of language in deductive reasoning is confined to an initial stage in which verbally presented information is encoded as non-verbal representations. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
43
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 79 publications
7
43
4
Order By: Relevance
“…On the other hand, a number of studies have failed to uncover any significant activation within Broca's area for propositional and categorical deductive inferences (Canessa et al, ; Kroger, Nystrom, Cohen, & Johnson‐Laird, ; Monti, Osherson, Martinez, & Parsons, ; Monti, Parsons, & Osherson, ; Noveck, Goel, & Smith, ; Parsons & Osherson, ; Rodriguez‐Moreno & Hirsch, ), even under much more naturalistic experimental conditions (Prado et al, ). An alternative hypothesis has thus been proposed under which logic is subserved by a set of language‐independent regions within frontopolar (i.e., BA10) and frontomedial (i.e., BA8) cortices, among others (Monti & Osherson, ; Monti et al, ). Consistent with this proposal, neuropsychological investigations have shown that lesions extending at through medial BA8 are sufficient to impair deductive inference‐making, as well as meta‐cognitive assessments of inference complexity, despite an anatomically intact Broca's Area and ceiling performance on neuropsychological assessments of language function (Reverberi, Shallice, D'agostini, Skrap, & Bonatti, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, a number of studies have failed to uncover any significant activation within Broca's area for propositional and categorical deductive inferences (Canessa et al, ; Kroger, Nystrom, Cohen, & Johnson‐Laird, ; Monti, Osherson, Martinez, & Parsons, ; Monti, Parsons, & Osherson, ; Noveck, Goel, & Smith, ; Parsons & Osherson, ; Rodriguez‐Moreno & Hirsch, ), even under much more naturalistic experimental conditions (Prado et al, ). An alternative hypothesis has thus been proposed under which logic is subserved by a set of language‐independent regions within frontopolar (i.e., BA10) and frontomedial (i.e., BA8) cortices, among others (Monti & Osherson, ; Monti et al, ). Consistent with this proposal, neuropsychological investigations have shown that lesions extending at through medial BA8 are sufficient to impair deductive inference‐making, as well as meta‐cognitive assessments of inference complexity, despite an anatomically intact Broca's Area and ceiling performance on neuropsychological assessments of language function (Reverberi, Shallice, D'agostini, Skrap, & Bonatti, ).…”
Section: Introductionmentioning
confidence: 99%
“…In what follows, we report on a 3T functional magnetic resonance imaging (fMRI) study in which we tested whether the pattern of activations that has been previously characterized as “core” to deductive inference (Monti et al, ; see Monti & Osherson, for a review) might instead reflect activity resulting from increased general non‐deductive cognitive load (a view we will label the general cognitive load hypothesis ). Specifically, using a 2 × 2 design (simple/complex, deductive/non‐deductive), we compare the effect of non‐deductive (e.g., working memory) versus deductive load on the putative “core” regions of deduction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…• Monti and Osherson (2012) report that, almost counter-intuitively, the role of language in reasoning is confined to an initial stage where verbally presented information is encoded as non-verbal representations. These are subsequently manipulated by mental operations that are not based on the neural mechanisms which handle natural language.…”
Section: Concept Creation and Rememberingmentioning
confidence: 99%
“…Using such logical structures, these studies have consistently reported activation of distributed cortical and sub-cortical networks, including those associated with language processing and semantic and visuo-spatial skills (see for review [10][15]). Lateralized effects have also been reported, with the left hemisphere playing a key role in linguistic processes and the right hemisphere mainly supporting logical reasoning [11], [12], [16], [17], although other studies have found key linguistic and logical processes to be in different sub-areas in the left hemisphere [5], [7], [8].…”
Section: Introductionmentioning
confidence: 99%